NITROGEN FERTILIZERS AND OCCURRENCE OF Leucoptera coffeella (Guérin-Mèneville & Perrottet) IN TRANSPLANTED COFFEE SEEDLINGS - Sabino, Paulo Henrique de Siqueira; Reis Junior, Francisco Ailton; Carvalho, Geraldo Andrade; Mantovani, José Ricardo (Coffee Science - ISSN 1984-3909, 2018)
The coffee leaf-miner (CLM) Leucoptera coffeella (Lepidoptera: Lyonetiidae) is one of the main pests of coffee plants in Brazil. Its occurrence in the crop is directly related to the physiological state and growth characteristics of coffee plants, in turn related to plant nutrition. The present work, therefore, aimed to evaluate the effect of nitrogen sources on the occurrence of CLM in coffee seedlings. The fertilizers used were ammonium sulfate, urea, and organomineral. The number of leaves mined by CLM and the relative contents of chlorophyll and crude protein in the leaves were recorded. Ammonium sulfate and urea favored higher occurrence of leaves mined and organomineral fertilizer provided the lowest incidence of leaves mined by CLM. The three sources of nitrogen increased the chlorophyll content, but only ammonium sulfate caused an increased percentage of crude protein in the leaves of coffee seedlings. For the improvement of management strategies for L. coffeella it is fundamental to understand favorable conditions, nutritional management it is one of the pest control mechanisms, thus making it possible to control the insect and prevent the population of CLM from reaching an economic damage threshold.